Influence of synthesis and processing parameters of the columbite precursor on the amount of Perovskite PMN - Cavalheiro, A.a. [UNESP]; Zaghete, M.a. [UNESP]; Santos, C.o. Paiva [UNESP]; Varela, J.a. [UNESP]; Longo, E. [UNESP] (ABM, ABC, ABPol, 1999)
Columbite route for synthesis of P3MgNb2O9 (PMN) allows the suppression of secondary phases in PMN powders. These phases, having low dielectric constant, affect negatively the dielectric properties of PMN ceramics. Aiming to get reactive PMN powders, the partial oxalate method was used to precipitate lead oxalate over MgNb2O6 particles. The columbite (NM) powders were prepared using polymeric precursor based on Pechini's method. Two processing routes were used to prepare PMN powders. In the first one the NM-lead oxalate co-precipitate was washed in water and ethanol and calcined at several temperatures. In the second route, the NM-lead oxalate co-precipitate was washed in water and isopropyl alcohol, ball milled for 30 min and calcined at several temperatures. The second route leads to practically pyrochlore free PMN. Powders morphologies observed by SEM showed the formation of agglomerates, which sizes depend on the processing route.
Keywords: synthesis; columbite; PMN; Perovskite